Ethnosains of The Javanese Community "The Body Funeral Process" as A Resource of Basic Science Learning - Winarto Winarto; Dwi Hesty Kristyaningrum; Aji Pamungkas; Putri Wulandari (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to reveal the natural science concept of the funeral process for the bodies of the Javanese people. This research is a qualitative research method of phenomonology. This research involved the Brebes community who carried out this activity. Data collection techniques used are interviews and scientific documents. The research instrument used was interviews. The validity of the data was obtained using the triangulation method. Data analysis techniques namely data reduction, presentation and drawing conclusions. The results of this study the process of burial of the bodies of the Brebes community includes 4 (four) activities: (1) bathing, (2) shrouding, (3) lighting, and (4) burying. The funeral process for bodies can be reconstructed into formal science/science at school. The depth of the grave is the standard measurement, which is 160 cm and 2 meters long and the height of the pile of soil is 75 cm. The circle that is placed on the head of the deceased serves as a pillow, 7 of which are placed between the neck and head, the hip area, and the feet. The body is laid on its side and facing the Qibla. The wood used as â€œtengerâ€/tombstone is of the teak/albasiar type. The body was closed using a board. The type of soil used for graves that has a loose texture. The types of flowers sprinkled over the grave are jasmine, magnolia, and roses. The process of treating the corpse has been carried out from generation to generation. The burial process of the corpse can be used as a learning resource for basic science courses in science teaching.